Sex-specific Predictors of Mortality in Patients with Heart Failure in Intensive Care Units Using Machine Learning - Tian, Xinhui (International Journal of Computer Science and Information Technology, 2025)
This retrospective cohort study analyzed congestive heart failure (HF) patients from MIMIC-IV and eICU-CRD. Statistical tests described patient characteristics, while machine learning models (CART, RF, XGBoost, LightGBM) ranked sex-specific predictors, with SHAP used for interpretation. Among 30,411 patients, 3,840 died (men: 12.7%, mean age 69.50; women: 12.6%, mean age 73.02). Systolic blood pressure (SBP) was more critical for mortality in women, while body temperature, blood urea nitrogen (BUN), and creatinine was more significant in men. This is the first machine learning study to explore sex-specific in-hospital mortality predictors in ICU HF patients, identifying both known and potentially important risk factors.